2022
DOI: 10.1007/s00340-021-07747-x
|View full text |Cite
|
Sign up to set email alerts
|

Optimized design of an all-optical XOR gate with high contrast ratio and ultra-compact dimensions

Abstract: In this work, an optimized structure of an XOR gate working in the optical domain is put for-ward to achieve high contrast ratio and extremely compact dimensions using a photonic crystal platform. The above structure employs silicon rods in a hexagonal lattice configuration. The design works purely on linear interference effect between the incoming light signals and does not involve any non-linear materials. The Finite Difference Time Domain based simulations are utilized to study the propagation of light with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…XOR gate with three input is one of the most crucial components for developing compressors. Using photonic crystal an all-optical XOR gate is developed by Anagha and Jeyachitra [14]. Although the device is exceptionally small dimension, it gives a high contrast ratio.…”
Section: Introductionmentioning
confidence: 99%
“…XOR gate with three input is one of the most crucial components for developing compressors. Using photonic crystal an all-optical XOR gate is developed by Anagha and Jeyachitra [14]. Although the device is exceptionally small dimension, it gives a high contrast ratio.…”
Section: Introductionmentioning
confidence: 99%
“…A recent paper [16] discusses the differences in characteristics between these topologies. Literature has shown that square and hexagonal lattices are commonly used [17,18], and operation can be performed in both linear and nonlinear regimes. Software packages such as RSOFT [19] (which uses the finite difference time domain (FDTD) numerical technique) and COMSOL [20] (i.e., which mainly operate on the finite element method (FEM)) are used to simulate and analyze (Ph.…”
Section: Introductionmentioning
confidence: 99%
“…In the other way, the term point defect was used to form cavity-based structures at the prescribed wavelength [54]. The removal of some rods from the structure will yield a waveguide that will help for passing light to reach the output port [55,56].…”
Section: Introductionmentioning
confidence: 99%